Penerapan Model Contextual Teaching and Learning (CTL) untuk Meningkatkan Keterampilan Menulis Teks Deskripsi pada Siswa Kelas V.C SDN 17 Pekanbaru - Nita Febri Yanti; Nurul Aulianisa; Siti Aulia Indah Febriana; Ummu Hani Hafizhah; Wilda Srihastuty Handayani Piliang (JURNAL ARMADA PENDIDIKAN, 2026)
This study was prompted by the low level of descriptive writing skills among pupils in Class V.C at SDN 17 Pekanbaru, which was caused by the predominance of the lecture method in teaching; as a result, pupils tended to be passive and were unable to develop their writing ideas in detail. The aim of this study was to describe the application of the Contextual Teaching and Learning (CTL) model in improving pupils’ descriptive writing skills. This study employed a qualitative descriptive approach, with 27 pupils in Class V.C at SDN 17 Pekanbaru as the research subjects. Data were collected through observation, interviews, and pre- and post-tests using an assessment rubric comprising seven indicators: text structure; richness of content and descriptive detail; use of adjectives; vocabulary choice; accuracy of spelling and punctuation (PUEBI); neatness and completeness of writing; and contextual elements of CTL. The research findings indicate that the implementation of the CTL model was able to improve pupils’ descriptive writing skills across almost all assessment indicators. Pupils became more active in observing their surroundings, found it easier to generate ideas for their writing, and began to use more appropriate and varied vocabulary and adjectives. However, the neatness and accuracy of their writing still need to be improved through further practice. This study concludes that the CTL model is effective as an alternative approach to teaching descriptive writing in primary schools, as it links the subject matter to pupils’ real-life experiences, thereby making learning more meaningful.